Credible Commitments: Further Remarks - Williamson, Oliver E. (American Economic Review, 2016)
I distinguish between unilateral and bilateral trading relations in an earlier article in this Review (1983) in which I examined the use of hostages (or their commercial equivalents) to support exchange. The purposes of this note are 1) to confirm the optimality of reciprocal trading by explicitly displaying the combined net benefit relations, and 2) to acknowledge a previously unremarked complication that arises when nonsalvageable assets are used as hostages in a unilateral trade.